Examining the effect of full-mission simulation training on the safety and education in the maritime sector - Ashraf Mohamed Elsayed; Hany Sobhy Ibrahim (Maritime Research and Technology)
This contemporary research assesses full-mission simulation as a training tool incorporated within the curriculum of the Arab Academy for Science, Technology and Maritime Transport with focus on operational safety and education aspects. Using a structured SWOT approach in the research the internal strengths and weaknesses as well as external opportunities and threats related to the full mission tool are shown. The simulator is very effective in simulating the marine environment and providing trainees with practical exercises, however, there are problems such as high usage costs and the risk of overwhelming the trainees. This study seeks to mitigate this problem by proposed a concurrent use of VR interoperability with full-mission simulator. This is anticipated to improve the quality of the training, cut down the training costs and increase the capability of developing different scenarios. Combining these systems in training and simulation proposes wide advantages including an efficient and logical program that ensures efficient outcomes. From the study VR integration is the way forward in addressing the challenges faced currently and also helping the Academy remain on top of maritime education and training development Received: 01 September 2024 Accepted: 30 October 2024 Published: 17 November 2024